Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Finally the third issue of the third year, JIFAM 3(3) December 2021, can be published. We feel very fortunate since, this issue consists of 5 papers, in which 3 papers from Indonesia, 1 paper from Nigeria and 1 paper from Malaysia. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the Third volume.